Colonial Debts The Case of Puerto Rico - Zambrana, Rocio (Duke University Press, 2021)
Rocío Zambrana uses the current political-economic moment in Puerto Rico to outline how debt functions as both an apparatus that strengthens neoliberalism and the island's colonial relation to the United States.